MODERN APPROACHES TO TREATMENT OF PATIENTS WITH PURULO-NECROTIC LESIONS OF DIABETIC FOOT SYNDROME - Kizimenko, A.A.; Gorodova-Andreeva, T.V.; Lyakhovskiy, V.I. (World of Medicine and Biology, 2018)
Since 1950, International Diabetic Federation has recorded a steady, unceasing growth in pandemic rates of diabetes incidence. According to some prognoses, by 2040, the number of patients with diabetes will exceed 500 million people. As for the Ukrainian statistics of 1 million 300 thousand, which corresponds to 3% of the total population (as of 2016), the declared quantitative indicators raise doubts and are only “the tip of the iceberg”. WHO estimates the approximate number of such patients in Ukraine at the level of 6-8%, which is equivalent to 2.5 million people. Accordingly, the number of complications increases and, as a consequence, rises the percentage of patients in need of surgical treatment. About 40% of diabetics sooner or later encounter various purulent-necrotic complications of diabetic foot syndrome. Treatment of such patients is laborious and long-lasting. Lesions of the lower extremities in patients with diabetes cause serious socio-economic damage to the society. Prevention and treatment of DFS consume enormous material resources that absorb about 10% of national health budgets, reaching 4.6-13.7 billion in different countries. This is due to the fact that in many countries of the world this problem is considered as medical and social. The medical community of the world develops and implements clinical practice recommendations and comprehensive programs for the treatment of patients with DFS. Recently, surgical treatment of purulent necrotic processes is aimed at implementation of organ-preserving interventions on the lower limbs of DFS patients – surgical debridement and “minor” amputations. A significant part of such interventions leads to extensive wounds, in which, against the background of the DM, the wound process is disturbed. It slows down the processes of wound healing and promotes process chronization, worsening the results of treatment. Therefore, new methods of local wound treatment are being sought, which include the use of modern dressings, laser therapy, ultrasound cavitation, and the like. One of the modern and perspective directions of wound treatment is vacuum therapy, which is increasingly used in the treatment of DFS with a positive effect. According to some researchers, this method is indicated for the treatment of wound defects in DFS, since it allows us to create the most favorable conditions for healing. However, in the studies focused on the place and role of vacuum therapy in the treatment of DFS, there is a series of contradictions concerning the indications, techniques and technology of the latter. The effect of vacuum on the course of acute and chronic wounds in patients with DFS also requires further differentiated study, depending on the pathogenetic form of injury, in order to develop the best indications and methods of using this method. This will improve the results of DFS surgical treatment and reduce the number of high amputations. Together, this determined the relevance of this study. Thus, based on the studied literature sources, we can conclude that vacuum therapy is an effective remedy for a number of purulent-necrotic complications of DFS and may be useful in the comprehensive treatment of such patients. However, it is necessary to continue to study the mechanisms of the influence of vacuum therapy on various parts of the wound process with specific purulent-necrotic complications, and to improve the treatment regimens with the use of negative pressure therapy.